Evaluation of the quality of imported dermo-aesthetic products and the satisfaction of customers of a pharmaceutical company in Lima, Peru (2022) - Alderete-Espejo, Hattie (2023)
Objective. To determine the relationship between the quality of imported dermo-aesthetic products and customer satisfaction of a pharmaceutical company in Lima, Peru 2022. Methods. The study had a quantitative, observational, cross-sectional and descriptive non-experimental design. The non-probabilistic sample consisted of 119 users. Two validated questionnaires were applied to measure product quality and customer satisfaction based on the Likert scale; likewise, cronbach's alpha was used for instrument reliability. Spearman's rho test was used for inferential analysis. Results. For the quality variable and its dimensions, we found ratings above 4, that is, above the satisfied scale. The dimension with the highest rating was safety (4.57), followed by responsiveness (4.47), the rest having similar values, but slightly lower. Regarding the satisfaction variable, the dimensions of level of satisfaction and perceived performance stood out with an average of 4.3, followed by the dimension of expectations with 4.2. Conclusion. There is a significant and direct relationship between the quality of imported dermoesthetic products and customer satisfaction; with Spearman's Rho correlation coefficient equal to 0.874 and Sig.<0.001.